2001
DOI: 10.1109/5326.983927
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking in social context: structural influences and receipt of information benefits

Abstract: Abstract-Research in the information processing, situated learning, and social network traditions has consistently demonstrated the importance of social networks for acquiring information. However, we know little about how organizational relationships established by a relative position in a formal structure or social relationships established by interpersonal processes influence whom is sought out for various kinds of information. Prior research suggests that people often receive some combination of five benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 80 publications
6
87
0
1
Order By: Relevance
“…Collaboration between the government, the aquaculture industry, and other stakeholders is necessary to utilize the total knowledge of all parties and balance legitimate competing interests, and improve overall governance. The empirical data in this paper illustrates that collaboration is an important source for actionable knowledge, and this is in line with earlier research (Cross, Rice, & Parker, 2001), which shows that task interdependence, here described as externalities, is the strongest and most consistent predictor of information seeking.…”
Section: Discussionsupporting
confidence: 90%
“…Collaboration between the government, the aquaculture industry, and other stakeholders is necessary to utilize the total knowledge of all parties and balance legitimate competing interests, and improve overall governance. The empirical data in this paper illustrates that collaboration is an important source for actionable knowledge, and this is in line with earlier research (Cross, Rice, & Parker, 2001), which shows that task interdependence, here described as externalities, is the strongest and most consistent predictor of information seeking.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that source-channel combinations fulfill various roles during the information seeking process (i.e., orientation or exploration, exchange of information, to gain certainty). This is comparable to findings of Cross, Rice and Parker (2001). They found that people receive various benefits from other people (i.e., sources) when seeking information.…”
Section: Flow and Length Of The Information-seeking Processsupporting
confidence: 82%
“…In fact, knowledge is more complex and based on experience (Cross, Rice, & Parker, 2001;Kram & Isabella, 1985;Morrison, 2002). It is therefore difficult to transfer knowledge and experiences from one individual to another.…”
Section: Studying Network In the Public Sectormentioning
confidence: 99%